FACTORS AFFECTING INTELLECTUAL CAPITAL PERFORMANCE WITH PROFITABILITY AS MODERATING VARIABLES IN COMPANIES IN THE LQ-45 INDEX IN INDONESIA STOCK EXCHANGE, 2015-2017 - Putri, Desyana (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study was to determine and analyse the factors that affect intellectual capital performance in companies incorporated in the LQ-45 index in the Indonesia Stock Exchange. The dependent variable in this study is intellectual capital performance. Employee productivity, firm size and board size as independent variables and profitability as moderating variables. The object of this research is companies incorporated in the LQ-45 index on the Indonesia Stock Exchange in 2015-2017. The sampling technique uses saturated samples. The research sample consisted of 54 companies with 162 units of analysis. Data analysis method is secondary data using SPSS (Statistical Package for the Social Sciences). The results of this study indicate that employee productivity has a positive and significant effect on intellectual capital performance. Firm size has a negative and significant effect on intellectual capital performance. Board size has no effect on intellectual capital performance. The profitability variable is not able to moderate the effect of employee productivity, firm size and board size on intellectual capital performance.